The innovative warehouse activities of Gyermelyi Holding Plc. pasta factory - Egressy, Dóra; Lados, Kitti; Csáki, Dávid; Rácz, Georgina (Studia Mundi – Economica, 2015)
The aim of this study is to analyze the logistic processes of the innovative warehouse of Gyermelyi Holding Plc. and its effects on the company. If the logistic processes are built appropriately, then due to the decrease of expenses incurred, it improves the efficiency of the company’s operations. For the research, we are mainly concentrating on the scientific investigation of the amount of shipped products, the rate of pick-ups and the formation of the workforce fluctuation. We survey the reason why this company wanted to make a unique investment happen, how this effected the market share and the company’s revenue. The findings of the research are based on the interview that we had with the managers of the company. The results of the innovation have been worked out by using a variety of statistical methods. In conclusion, by comparing the before and after status of the warehouse enlargement, we can confidently state that this long-term investment is rewarding for the company. Using an innovative warehousing technique can lead to a significant improvement in the logistic processes, as well as support the implementation of future goals.